U.S. Sanctions and the Russian Arctic:The Oil and Gas Sector as Russia’s Achilles’ heel? - Kirchner, Stefan (SSRN Electronic Journal, 2019)
The territorial dispute between Russia and Ukraine, which has been going on since the illegal annexation of Crimea by Russia in 2014, is now starting to show effects also far away from the battlefields of Eastern Ukraine: in the waters of the Arctic Ocean, off the shores of Russia’s far north. US sanctions against Russia have recently had a direct impact on the ability of the hydrocarbon sector to operate as planned. In this text, it will be shown that the very sector on which the current Russian government seems to pin a lot of hope for the country’s economic development, the oil and gas sector, might turn out to become Russia’s weakness in the future. In this investigation, US sanctions against Russia are put into the wider context of their effects on non-US actors, in particular companies from the Arctic and Nordic countries, as well as into the wider context of international law. It will be shown that, although the Russian oil and gas industry is perceived as a key element of the Russian economy today, the dependence on non-Russian technology, combined with the effective implementation of US sanctions against Russia, might turn out to be an effective lever for change in Moscow.